A taste of history - Staib, Walter (Philadelphia, Pa. : Concepts by Staib, 2013)
Advertising cards promoting a PBS cooking show called A Taste of History, starring Walter Staib.
[1] Great chefs are born!: Walter Staib at age 4 -- [2] A Taste of History: Chef Walter Staib -- [3] Chef Walter Staib's A Tatse of History -- [4] Enjoy A Taste of History with the ales of the Revolution -- [5] Chef Walter Staib presents a tribute to Benjamin Franklin -- [6] A Taste of History: an evening with Cef Staib -- [7] The first five presidents: A Tates of History collector's edition.
Title supplied by cataloguer.
Keywords: Cooking, American; Staib, Walter; Franklin, Benjamin; Jefferson, Thomas; Lighthizer, Becky; Maguire, Sarah; Bell, Sheila; Yards Brewery (Philadelphia, Pa.); City Tavern (Philadelphia, Pa.); Ale; Orchester, Bill; Edenbo, Steve; Restaurants -- Pennsylvania -- Philadelphia; German Americans